App-based data collection, mental imagery, and naming performance in adults with aphasia. (August 2021) - Laures-Gore, Jaqueline; Stache, Monika; Moore, Elliot; Tullis, Chris
Abstract: Background and purpose: Naming impairments are often found in aphasia. Combining mHealth technology with mental imagery may offer new insights into novel approaches to naming interventions in persons with aphasia. The aims of this study are to (1) explore whether mental imagery can improve performance during a naming task in adults with aphasia; and, (2) demonstrate the use of app-based data collection for research in aphasia rehabilitation through utilization of an app designed specifically for this study. Materials and methods: A single subject non-concurrent multiple baseline design across participants was utilized. Four participants with anomic and conduction aphasia were included. Each participant's percentage of naming accuracy was measured before the initiating intervention to establish a baseline level of performance. Results: Per overlap metrics, two of the participants demonstrated a strong effect in improving naming from baseline to intervention on items using the app. Two participants showed no effect in naming accuracy from the imagery intervention. Conclusion: Some participants showed improvement in naming items following an imagery script, suggesting that this complementary health practice should continue to be explored. Additionally, this study demonstrates the successful use of app-based data collection. Highlights: A mobile application was successfully used for data collection in aphasia rehabilitation research. There were mixed results regarding the use of imagery on naming performance. Mental imagery and its application to naming in aphasia should be further explored.